Geochemical characteristics of tight gas and gas-source correlation in the Daniudi gas field, the Ordos Basin, China. (January 2017) - Wu, Xiaoqi; Liu, Quanyou; Zhu, Jianhui; Li, Kuang; Liu, Guangxiang; Chen, Yingbin; Ni, Chunhua
Abstract: The molecular composition, stable carbon and hydrogen isotopes and light hydrocarbons of the Upper Paleozoic tight gas in the Daniudi gas field in the Ordos Basin were investigated to study the geochemical characteristics. Tight gas in the Daniudi gas field displays a dryness coefficient (C1 /C1–5 ) of 0.845–0.977 with generally positive carbon and hydrogen isotopic series, and the C7 and C5–7 light hydrocarbons of tight gas are dominated by methylcyclohexane and iso-alkanes, respectively. The identification of gas origin and gas-source correlation indicate that tight gas is coal-type gas, and the gases reservoired in the Lower Permian Shanxi Fm. (P1 s) and Lower Shihezi Fm. (P1 x) had a good affinity and were derived from the P1 s coal-measure source rocks, whereas the gas reservoired in the Upper Carboniferous Taiyuan Fm. (C3 t) was derived from the C3 t coal-measure source rocks. The molecular and methane carbon isotopic fractionations of natural gas support that the P1 x gas was derived from the P1 s source rocks. The differences of geochemical characteristics of the C3 t gas from different areas in the field suggest the effect of maturity difference of the source rocks rather than the diffusive migration, and the large-scale lateral migration of the C3 t gas seems unlikely. Comparative study indicates that the differences of the geochemical characteristics of the P1 s gases from the Yulin and Daniudi gas fields originated likely from the maturity difference of the in-situ source rocks, rather than the effect of large-scale lateral migration of the P1 s gases. Highlights: The Daniudi tight gas is coal-derived based on the geochemical characteristics. The P1 s–P1 x and C3 t gas were derived from P1 s and C3 t source rocks, respectively. Large-scale lateral migration seems unlikely to occur for the Daniudi tight gas.